Bereavement and cancer: some data on deaths of spouses from the longitudinal study of Office of Population Censuses and Surveys. Issue 6443 (25th August 1984) - Jones, D R; Goldblatt, P O; Leon, D A
Abstract : Registration of cancer and mortality after the death of a spouse were assessed using data from the longitudinal study of the Office of Population Censuses and Surveys (OPCS). The study population comprised 1% of the people counted in England and Wales in the 1971 census, for whom data on subsequent vital events were linked with their census records. There was little evidence of an increase in registrations of cancer after the death of a spouse and only a slight suggestion of increased mortality from cancer. For other causes of death there was some evidence of increases in mortality during widow(er)hood. In so far as the death of a spouse is often a very stressful event, these data may be interpreted as providing little support for the hypothesis that stress is implicated in the aetiology of cancer.